Prodigiosin Sensitizes Sensitive and Resistant Urothelial Carcinoma Cells to Cisplatin Treatment - Berning, Lena (Molecules, 2021)
Cisplatin-based treatment is the standard of care therapy for urothelial carcinomas. However, complex cisplatin resistance mechanisms limit the success of this approach. Both apoptosis and autophagy have been shown to contribute to this resistance. Prodigiosin, a secondary metabolite from various bacteria, exerts different biological activities including the modulation of these two cellular stress response pathways. We analyzed the effect of prodigiosin on protein levels of different autophagy- and apoptosis-related proteins in cisplatin-sensitive and -resistant urothelial carcinoma cells (UCCs). Furthermore, we investigated the effect on cell viability of prodigiosin alone or in combination with cisplatin. We made use of four different pairs of cisplatin-sensitive and -resistant UCCs. We found that prodigiosin blocked autophagy in UCCs and re-sensitized cisplatin-resistant cells to apoptotic cell death. Furthermore, we found that prodigiosin is a potent anticancer agent with nanomolar IC(50) values in all tested UCCs. In combination studies, we observed that prodigiosin sensitized both cisplatin-sensitive and -resistant urothelial carcinoma cell lines to cisplatin treatment with synergistic effects in most tested cell lines. These effects of prodigiosin are at least partially mediated by altering lysosomal function, since we detected reduced activities of cathepsin B and L. We propose that prodigiosin is a promising candidate for the therapy of cisplatin-resistant urothelial carcinomas, either as a single agent or in combinatory therapeutic approaches.